Practical methods of conserving the soil moisture in Riley County - Harvey, John Andrew (My University, 1899)
Introduction: Our average rainfall in this part of the state for the past thirty years has been thirty inches per annum, an amount, which, if properly stored up until needed, would be sufficient to ensure us abundant crops. Yet, a careful study of the station record of the rainfall, shows that the rain has come at irregular intervals, often great quantities falling at once, and that there has usually been one or more periods of drought each season, which caused a greater or less shortage of crops. It is the object of this production to set forth, in a brief and informal manner, some of the views the writer has gathered on this subject.
Citation: Harvey, John Andrew. Practical methods of conserving the soil moisture in Riley County. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Methods of Tillage; Plowing; Subsoiling; Harrowing; Discing Stubble; Frequent Inter Tillage; Theses; Manuscripts (documents)